India's Post-Primary Education, Poverty, and Development (International Journal of Innovative Research in Engineering & Management, 2021)
Many policymakers believe that secondary and tertiary education  home schooling are not necessary for economic development and  progress. Literacy and early learning, on either hand, are seen as  critical. The formulation of such a notion was also supported by  predictions of the real interest rate. As a result, secondary and  higher education are not on many impoverished nations' or  foreign assistance organizations' poverty reduction agendas. All  of this is supported by the Indian experience. The administration  has mostly ignored secondary and, more importantly, tertiary  education. Using the most recent statistics, it is argued that the  general assumption that secondary and higher education play a  minor or non-existent role in development is inaccurate, and that  thread education is essential for reducing inequality, increasing  infant and child mortality and health status, and boosting  economic growth.
Keywords: Economic Growth; Higher Education; Life Expectancy; Poverty; Secondary Education